2014
DOI: 10.1055/s-0034-1390245
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of the Traumatic Orbital Apex Syndrome due to Direct Bone Compression

Abstract: Traumatic orbital apex syndrome is a well-known but rare complication of craniomaxillofacial trauma that combines features of the superior orbital fissure syndrome with traumatic optic neuropathy. The optimal treatment of traumatic orbital apex syndrome has not been established, because there have been so few cases. We report a case of traumatic orbital apex syndrome combined with the blow-in type of the orbital and zygomaticomaxillary complex (ZMC) fracture, which was successfully treated by emergency decompr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…[10][11][12] Third, ophthalmic veins appeared to avoid the thick common tendon when draining from the orbit. In radiologic evaluations of orbital apex syndrome, [13][14][15] it appears that no one has yet discriminated the tendon from the periosteum extending along the orbital fissure. Fourth, notably, in addition to this tendinous origin, we found that parts of the SR and/or LR fibers originated from the optic or oculomotor nerve sheath (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Third, ophthalmic veins appeared to avoid the thick common tendon when draining from the orbit. In radiologic evaluations of orbital apex syndrome, [13][14][15] it appears that no one has yet discriminated the tendon from the periosteum extending along the orbital fissure. Fourth, notably, in addition to this tendinous origin, we found that parts of the SR and/or LR fibers originated from the optic or oculomotor nerve sheath (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even minor craniofacial force might cause neurological disorders around the cranial apex region and thus lead to TOAS. According to degree of compression on imaging data, TOAS can be divided into two types: (1) direct damage resulting from fracture fragment, foreign bodies, or hematoma and (2) indirect damage resulting from secondary inflammation and edema [ 12 ]. It is widely acknowledged that hemorrhage inside the meningeal sheath, optic nerve swelling, and necrosis secondary to decreased blood flow could be the main pathology of TON.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Pletcher et al [ 17 ] proposed that simple steroid treatment might have worse prognosis compared with surgical decompression. Imaizumi et al [ 12 ] reported that one case receiving decompression of optic canal and SOF regained visual perception successfully. While in another study [ 10 ], 2 cases of TOAS underwent conservative treatment of steroid and vitamin B12 with one of them presenting no improvement and the other one presenting incomplete eye movement.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] This case illustrates all of the hallmarks of an OAS, which include visual loss from optic neuropathy, ophthalmoplegia resulting from multiple cranial nerves (oculomotor, trochlear, and abducens), and numbness in the territory of the ophthalmic branch of the trigeminal nerve. [ 1 2 ]…”
Section: Discussionmentioning
confidence: 99%